(untitled) (Bhartiya Knowledge Systems, 2024)
Particulate matter (PM) less than one-tenth of the size of a human hair coming out from vehicle emission may cause a serious health issues in a community. It is not less than endemic caused by current pollutants spit out by various transportation systems. The composition of particulate matter includes hydrocarbons, nitrogen oxides, benzene, Sculpture dioxide, 1, 3 buta diene, polycyclic aromatic hydrocarbons (PAHs), carbon monoxide (CO) and lead. Most of them can cause inflammation, allergic reactions or respiratory illnesses like apnea and short breathing. However, the polycyclic aromatic hydrocarbon present in vehicle emission can lead to severe deposition in human lung and other tissues. The consumption of poultry meat from a butcher shop present nearby emission of vehicles across the roads could be unhealthy. This may be, due to deposition and absorption of small fraction of particulate matters of emission. The consumption of such meat products causes the ingestion of polycyclic aromatic hydrocarbons (PAHs) as well. PAHs may cause lung and other cancers. Recent study highlights the importance of good practices and regulation of selling meat products for human consumption. The study explained and linked the molecular mechanism of cancer caused by cellular deposition of polycyclic aromatic hydrocarbons (PAHs).The possible methods to detect and quantify polycyclic aromatic hydrocarbons present in such meat products could be ensured to eliminate from the food chain.